ON DEVELOPMENT OF THE LYMPH AND BLOOD OF DOGS IN THE PROTEIN COMPOSITION UNDER SOME EFFECTS ON ORGANISMS - Myrzakhanov, N.; Myrzakhanova, M. N. (European Scientific Journal, ESJ, 2013)
﻿﻿﻿Investigation of our sciences shows that the distribution of proteins is not the same for all organs and tissues of the body and in various animal species. Because we studied the protein composition of intestinal lymph and blood plasma at rest and during stimulation of mechanoreceptors in the rectum, the peripheral segment of the lumbar splanchnic and central end of the hypogastric nerves in the intact innervation and after chronic decentralization of the caudal mesenteric sympathetic ganglion (CMSG) and some more visceral nerve transection. The experiments were performed on dogs weighing from 8 up 26 kg. For stimulation of the peripheral segment of the lumbar splanchnic and hypogastric nerves of the central segment used an electronic stimulator type ISE-01 (pulse width of 2 m/s, the frequency of 20 pulses/sec, the intensity of 5-10V). Irritation of mechanoreceptors rectum is achieved by injecting air into the cylinder (150-300 ml) syringe Janet. Before, during, and after 2-5 minutes blood samples were taken from the femoral artery and the common mesenteric vein after stimulation. The concentration of total protein in the blood and lymph refract metric is determined, and the amount of protein fractions is determined by paper electrophoresis. Thus, a comparison of the lymph and blood showed that a comparative study of the protein composition of body fluids allows us to study the quantitative changes in both the normal and the indicated effects on the body and in agreement with the literature data suggest that the lymphatic system of the intestine is involved in an adequate distribution of proteins between the blood and lymph, thereby providing fine regulation to changing internal and external environment, which once again clearly shows the close relationship between the circulatory and lymphatic systems.